A new modified B4 inverter using SRF controller with SVPWM technique for grid-connected PV system - Anitha, Golkonda; Kondreddi, Krishnaveni; Yesuratnam, Guduri (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
The integration of renewable power sources into the grid presents a complex challenge, as the grid operates at AC voltage, while photovoltaic (PV) arrays generate DC power. A 3-phase inverter synchronizes with the grid’s voltage and frequency for efficient energy integration. In conventional technique, a 3-ph 6-switch (B6) inverter is used for sharing the power to the grid. In this paper reduced switch count 3-ph 4-switch (B4) inverter topology is introduced with reduced power losses. This topology has 4 insulated gate bipolar transistor (IGBT) switches and two capacitors replacing the other 2 switches positioned in one leg of the inverter, which connects to a grid connected PV system. A grid synchronization method called synchronous reference frame (SRF) based proportional integral (PI) is used to track the phase angle of the grid and subsequently inject current into the grid. A B4 inverter is operated by a novel space vector pulse width modulation (SVPWM) control technique which operates in 4 possible switching states. A comparative analysis is carried out with the PV array grid integration connected through B4 and B6 inverter topologies with SRF control. The modeling and design are carried out in a MATLAB/Simulink environment with graphs plotted according to the conditions. The comparative analysis validates the importance of SRF controllers for the grid integration of any renewable source.